A bacterial DNA repair pathway specific to a natural antibiotic. Issue 2 (28th November 2018) - Burby, Peter E.; Simmons, Lyle A.
Summary: All organisms possess DNA repair pathways that are used to maintain the integrity of their genetic material. Although many DNA repair pathways are well understood, new pathways continue to be discovered. Here, we report an antibiotic specific DNA repair pathway in Bacillus subtilis that is composed of a previously uncharacterized helicase ( mrfA ) and exonuclease ( mrfB ). Deletion of mrfA and mrfB results in sensitivity to the DNA damaging agent mitomycin C, but not to any other type of DNA damage tested. We show that MrfAB function independent of canonical nucleotide excision repair, forming a novel excision repair pathway. We demonstrate that MrfB is a metal‐dependent exonuclease and that the N‐terminus of MrfB is required for interaction with MrfA. We determined that MrfAB failed to unhook interstrand cross‐links in vivo, suggesting that MrfAB are specific to the monoadduct or the intrastrand cross‐link. A phylogenetic analysis uncovered MrfAB homologs in diverse bacterial phyla, and cross‐complementation indicates that MrfAB function is conserved in closely related species. B. subtilis is a soil dwelling organism and mitomycin C is a natural antibiotic produced by the soil bacterium Streptomyces lavendulae . The specificity of MrfAB suggests that these proteins are an adaptation to environments with mitomycin producing bacteria. Abstract : Bacteria possess DNA repair pathways to maintain the integrity of their genetic material. The putative helicase MrfA and the exonuclease MrfB are part of a mitomycin C (MMC) specific DNA repair pathway in Bacillus subtilis . Despite being present in many bacterial species, MrfAB activity in repairing MMC damaged DNA appears to be restricted to closely related species, suggesting that despite sequence conservation these proteins have evolved to the specific repair needs of each bacterium.